Development of a Web-Based Village Tourism Management Information System to Support Sustainable Tourism Destinations - Tuhuteru, Hennie; Palyama, Dessy Gloria; Ferdinandus, Junioverrill Gavriel; Metiary, Desya Y (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
Digitalization in local tourism development is essential as it significantly impacts the growth and sustainability of Tourism Villages. This study aims to develop a website-based Tourism Management Information System to support sustainable tourism development in Tourism Villages in Maluku. The Rapid Application Development (RAD) method was utilized to build the system, consisting of four stages: Requirement Planning, User Design (Iterative: prototype, testing, and refinement), Construction, and Cutover. The iterative process during the User Design stage accelerated system development by continuously incorporating user feedback and needs. System testing employed usability testing during the User Design phase and black-box testing during the Construction phase. The results of this study demonstrate that the developed system successfully fulfills user requirements, enhancing the management and accessibility of Tourism Villages. Key features include tour package selection and an online reservation system, simplifying travel arrangements for visitors. This system significantly impacts tourism development by improving operational efficiency, promoting local attractions, and fostering economic growth in Tourism Villages. Furthermore, the system contributes to the sustainability of tourism by encouraging digital transformation, increasing visitor engagement, and supporting local communities through enhanced tourism services.